2012
DOI: 10.1186/1471-2407-12-485
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib modulates the radio sensitivity of hepatocellular carcinoma cells in vitro in a schedule-dependent manner

Abstract: BackgroundHepatocellular carcinoma (HCC) has a high incidence and mortality. Radiotherapy and sorafenib have proven effective for HCC. Here, we investigated whether sorafenib modulated the response of HCC cells to irradiation in vitro, effect of timing of sorafenib, and the underlying mechanisms.MethodsCell viability of the HCC cell lines, SMMC-7721 and Bel-7402, was examined by the 3-(4,5-dimethylthiazol-2-yl)-5(3-carboxymethoxyphenyl)-2(4-sulfophenyl)-2 H-terazolium (MTT) assays. Clonogenic growth assays of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…To investigate the activity of combined sorafenib and radiation against HCC, we tested concurrent and sequential treatment approaches in four HCC cell lines. Using colony formation assays, we found that a sequential approach produced an additive increase in efficacy, while concurrent therapy resulted in radioprotection or no effect when compared to radiation alone, corroborating the results of Li and colleagues [36]. Based on previous work in non-HCC cell lines [29], we hypothesized that this effect of concurrent treatment might be due to sorafenib-mediated reassortment into less radiosensitive phases of the cell cycle and generalized cell cycle slowing.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To investigate the activity of combined sorafenib and radiation against HCC, we tested concurrent and sequential treatment approaches in four HCC cell lines. Using colony formation assays, we found that a sequential approach produced an additive increase in efficacy, while concurrent therapy resulted in radioprotection or no effect when compared to radiation alone, corroborating the results of Li and colleagues [36]. Based on previous work in non-HCC cell lines [29], we hypothesized that this effect of concurrent treatment might be due to sorafenib-mediated reassortment into less radiosensitive phases of the cell cycle and generalized cell cycle slowing.…”
Section: Discussionsupporting
confidence: 86%
“…Several ongoing phase I–II trials employ sorafenib and radiation concurrently, sequentially, or both (Table 1); however, preclinical data examining sorafenib and radiation in HCC that might guide selection of the optimal therapeutic sequence for clinical use is limited to one in vitro study, which did not involve any in vivo experiments [36]. To investigate the activity of combined sorafenib and radiation against HCC, we tested concurrent and sequential treatment approaches in four HCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine kinase inhibitors are crucial in systemic treatment of HCC as they hinder tumor progression and improve overall survival rate [9]. Some studies have concluded that sorafenib also may enhance tumor sensitivity to radiotherapy [10]. Patients with metastases from HCC can benefit from radiotherapy in terms of prolonged survival [11].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that inhibition of NF-κB activation and the expression of its downstream proteins by pretreatment of sorafenib may increase TSA-induced apoptosis and cell death. A previous study suggested that the radiosensitivity of HCC cells may be modulated by sorafenib in a schedule-dependent manner (28). Furthermore, concurrent treatment with radiation and sorafenib and pre-treatment of sorafenib were reported to improve the sensitizing enhancement ratio for human SMMC-7721 and SK-HEP-1 HCC cell lines, respectively (29).…”
Section: Discussionmentioning
confidence: 99%